2015
DOI: 10.7326/m15-0667
|View full text |Cite|
|
Sign up to set email alerts
|

Alexander Technique Lessons or Acupuncture Sessions for Persons With Chronic Neck Pain

Abstract: Arthritis Research UK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(72 citation statements)
references
References 34 publications
2
65
0
Order By: Relevance
“…The lessons were delivered over a 12 week period, twice a week for the first 8 weeks and weekly for the final 4 weeks. This rate of delivery was chosen to ensure similarity with other clinical trials investigating the AT, as well as with routine practice [31, 32]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lessons were delivered over a 12 week period, twice a week for the first 8 weeks and weekly for the final 4 weeks. This rate of delivery was chosen to ensure similarity with other clinical trials investigating the AT, as well as with routine practice [31, 32]. …”
Section: Methodsmentioning
confidence: 99%
“…For example AT lessons have been shown to improve clinical outcomes in people with chronic low back [31], reduce pain in individuals suffering with neck pain [32] and also to improve self-reported disability and depression in people diagnosed with Parkinson’s disease [33]. Research has also demonstrated that training in the AT can improve neuromuscular coordination and enhance the dynamic regulation of postural tone [34, 35].…”
Section: Introductionmentioning
confidence: 99%
“…15 In an interview, Laine pointed to a trial her journal and the COMPare team had tussled over for months (box 1).…”
Section: Journal Dissentmentioning
confidence: 99%
“…The journal's editor, Jeffrey Drazen, has been a longtime supporter of trial registration, [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] and NEJM was the first of its peers to publish trial protocols alongside trial publications, a practice now followed by JAMA, The BMJ, and most recently-in part thanks to COMPare 27 -Annals.…”
Section: Journal Dissentmentioning
confidence: 99%
See 1 more Smart Citation